2020
DOI: 10.22454/fammed.2020.676654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clinic First Educational Interventions on Resident Wellness and Engagement

Abstract: Background and Objectives: Tensions between clinical and hospital training, along with dysfunctional family medicine training clinics, have resulted in continuity clinic being the least favorite part of training for some residents. These factors are all contributors to burnout. We hypothesized that following Clinic First action steps to prioritize and enhance outpatient clinic would positively affect resident wellness and clinic engagement. This study describes our interventions and their effects within the Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The evidence of convergent validity showed that dispositional hope obtained a positive association with work engagement, evidencing that dispositional hope may promote higher levels of positive work well-being states (Hofkamp et al, 2020 ; Sarfraz et al, 2019 ). Also, following hypothesis 4, dispositional hope was negatively associated with burnout and its dimensions, showing that higher levels of hope may act as a protective factor to prevent the development of burnout (Hofkamp et al, 2020 ; Passmore et al, 2020 ; Yotsidi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence of convergent validity showed that dispositional hope obtained a positive association with work engagement, evidencing that dispositional hope may promote higher levels of positive work well-being states (Hofkamp et al, 2020 ; Sarfraz et al, 2019 ). Also, following hypothesis 4, dispositional hope was negatively associated with burnout and its dimensions, showing that higher levels of hope may act as a protective factor to prevent the development of burnout (Hofkamp et al, 2020 ; Passmore et al, 2020 ; Yotsidi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of convergent validity showed that dispositional hope obtained a positive association with work engagement, evidencing that dispositional hope may promote higher levels of positive work well-being states (Hofkamp et al, 2020 ; Sarfraz et al, 2019 ). Also, following hypothesis 4, dispositional hope was negatively associated with burnout and its dimensions, showing that higher levels of hope may act as a protective factor to prevent the development of burnout (Hofkamp et al, 2020 ; Passmore et al, 2020 ; Yotsidi et al, 2018 ). The protective role that dispositional hope plays in the context of the professionals’ work shows that it is characterized as a personal resource that contributes to planning their professional goals and driving their actions to achieve them (Snyder et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, training programs for outpatient teaching and ward teaching should differ in terms of both training patterns and training priorities. The “clinic first model” of general practice residency training aims to improve the quality of patient management and the participation of residents in ambulatory teaching programs [ 2 4 ]. According to the Chinese Medical Doctor Association (CMDA) [ 5 ], ambulatory teaching is a key part of standardized residency training that focuses on promoting the residents’ ability to independently manage outpatients under the supervision of preceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Emphasizing the importance of our learners, Dr Hofkamp et al describe the potential of curricular changes in ambulatory settings to improve resident engagement and foster their well-being, demonstrating improvement in resident self-perception of personal wellness and preparedness reflected in postimplementation survey results. 16 The final paper addresses the need for today's family physicians to possess practice management acumen, positing that an understanding of financial issues and quality improvement is key to innovative and sustainable practice. The article demonstrates that practice management residency curricula can lead to an increase in resident ability to subsequently implement processes that will improve patient care.…”
mentioning
confidence: 99%